Pengaruh Remunerasi dan Disiplin Kerja Terhadap Kinerja Pegawai pada Kantor Pelayanan Pajak (KPP) Pratama Raba Bima - Sri Rahayu; Firmansyah Kusumayadi; Mawar Hidayanti (CV Edujavare Publishing, 2026)
This study aims to analyze the effect of remuneration and work discipline on employee performance at the Tax Service Office (KPP) Pratama Raba Bima. The study employed a quantitative associative approach involving 44 employees selected through purposive sampling from a population of 64 employees. Data were collected using questionnaires, observations, and literature studies. The collected data were analyzed using multiple linear regression with IBM SPSS Statistics after passing validity, reliability, and classical assumption tests. The findings indicate that remuneration has no significant effect on employee performance (t = 1.243; p = 0.221), while work discipline has a positive and significant effect on employee performance (t = 2.145; p = 0.038). Simultaneously, remuneration and work discipline significantly influence employee performance (F = 3.533; p = 0.038), with a coefficient of determination (R²) of 0.847, indicating that 84.7% of the variation in employee performance can be explained by the two independent variables. These findings suggest that improving employee performance depends more on strengthening work discipline than solely enhancing remuneration. Therefore, organizations are encouraged to reinforce disciplinary practices while continuously evaluating remuneration systems to ensure fairness, transparency, and alignment with employee responsibilities and performance.